The impact of brotherhoods in Allah in achieving self- security - Majdoubeh, Samira Ahmed (Journal of Islamic Sciences, 2019)
The brotherhood and love in Allah is one of the great blessings that Allah offers to faithful believer which draw among our hearts and from brotherhood among our souls together that has deep effect in their lives and in the stability of their souls. Brotherhood is one of the successful methods in spreading easiness and self confidence in the human Soule. This present good relationship among Muslims in spreading affection and harmony among people. In this research I have discussed the concept of brotherhood in Islam and its priority in Al- Quran and Sunna on the members of the society referring to the explanation books and pointing to the interest of Quran and Sunna in achieving the psychological security. I have used the library and analysis methodology in the whole knowledge, and shows the effect of brotherhood on the happiness and peace of people is minds.